2010
DOI: 10.1111/j.1399-5448.2010.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Determinants of Diabetes in the Young (TEDDY) Study: predictors of early study withdrawal among participants with no family history of type 1 diabetes

Abstract: Objective-The Environmental Determinants of Diabetes in the Young (TEDDY) study seeks to identify environmental triggers of autoimmunity and type 1 diabetes (T1DM) in children at increased HLA-conferred genetic risk for this disease. This study's objective was to identify predictors of early withdrawal from TEDDY among families with no immediate family history of T1DM.Method-Logistic multiple regression was used to discriminate 2994 (83%) families currently active in the TEDDY study for ≥ 1 year from 763 (17%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 10 publications
5
54
0
Order By: Relevance
“…More educated mothers with accurate perceptions of their child's T1DM risk, who had been in the TEDDY study longer and who rarely -if ever -missed a TEDDY visit, were more likely to return the questionnaire. We previously reported that mothers who accurately estimate their child's risk for TIDM are more likely to stay in the TEDDY study during the first year [10], a finding that is consistent with the current study's finding that mothers with accurate TDIM risk perceptions were more likely to return the questionnaire. Because more committed families were more likely to return the survey, the results are likely biased and represent the opinions of those most involved in the TEDDY study.…”
Section: Discussionsupporting
confidence: 81%
“…More educated mothers with accurate perceptions of their child's T1DM risk, who had been in the TEDDY study longer and who rarely -if ever -missed a TEDDY visit, were more likely to return the questionnaire. We previously reported that mothers who accurately estimate their child's risk for TIDM are more likely to stay in the TEDDY study during the first year [10], a finding that is consistent with the current study's finding that mothers with accurate TDIM risk perceptions were more likely to return the questionnaire. Because more committed families were more likely to return the survey, the results are likely biased and represent the opinions of those most involved in the TEDDY study.…”
Section: Discussionsupporting
confidence: 81%
“…Selection bias is likely as age of mother, country, education and other factors were associated with dropout rate in the TEDDY study [34, 35]. Misclassification of infections, as discussed for enterovirus infections, was an important limitation.…”
Section: Discussionmentioning
confidence: 99%
“…To establish the origin and changes associated with the development of type 1 diabetes, careful selection of appropriate study groups is essential, such as have been established by prospective sampling from at-risk individuals (7,8). The Finnish Type 1 Diabetes Prediction and Prevention (DIPP) project collected samples from Finnish children with HLA-defined predisposition to type 1 diabetes (7,9), thus creating an extensive prospective sample collection from birth to diagnosis or otherwise healthy until 15 years of age.…”
mentioning
confidence: 99%